2019
DOI: 10.1007/s13181-019-00746-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effectiveness of Online Learning Modules in Pediatric Environmental Health Education

Abstract: Objective Content and training about pediatric environmental health are lacking in healthcare professionals' education. In an initiative to improve pediatric environmental health education, the Pediatric Environmental Health Specialty Unit (PEHSU) program offers free, interactive, web-based ("eLearning") modules on environmental health topics. The aim of this study is to determine the effectiveness of PEHSU eLearning modules in increasing knowledge about pediatric and reproductive environmental health. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…A study about e-learning in palliative care showed that 96% of students used e-learning as a preparation tool for their exams (27). Another survey for evaluating the effectiveness of an online teaching module in the pediatric department showed that e-learning is effective at increasing environmental health knowledge of clinical and non-clinical professionals, assessed by a pre-test and a post-test for the clinical expertise acquired from the online modules (28). Others have shown that educational technologies for respiratory care have an important role and that online learning for baccalaureate and higher degrees in respiratory care is promising.…”
Section: Knowledge Attainmentmentioning
confidence: 99%
“…A study about e-learning in palliative care showed that 96% of students used e-learning as a preparation tool for their exams (27). Another survey for evaluating the effectiveness of an online teaching module in the pediatric department showed that e-learning is effective at increasing environmental health knowledge of clinical and non-clinical professionals, assessed by a pre-test and a post-test for the clinical expertise acquired from the online modules (28). Others have shown that educational technologies for respiratory care have an important role and that online learning for baccalaureate and higher degrees in respiratory care is promising.…”
Section: Knowledge Attainmentmentioning
confidence: 99%
“…Since the emergence of the COVID-19 pandemic, all areas of distant communication and learning were accelerated, this change being permanent in many ways. 14 Although it may be feasible for e-learning to replace classroom setting education in some elds entirely, medical education is heavily reliant on student-patient interaction, bed-side learning, and in-person attendance of surgical procedures and teaching rounds. This could pose a challenge to the incorporation of elearning into medical teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Digitale Formate werden bereits seit vie-lenJahrenfürdasMedizinstudiumentwickelt, wobei dies jedoch häufig für spezielle Fragestellungen erfolgte, wie die Verschreibung von Medikamenten, das Erlernen pädiatrischer Reanimationstechniken, die Bearbeitung umweltmedizinischer Fragen oder spezielle dermatologische oder physiologische Lehrinhalte [1][2][3][4][5][6] Studierenden mit digitalen Lehrformaten beeinflussen, sind die Leistungsansprüche der Studierenden an sich selbst sowie das Lernklima. Gleichzeitig sind digitale Lehrformate nach bisherigen wissenschaftlichen Analysen zeit-, kostenund arbeitsintensiv und weniger geeignet für die Vermittlung praktischer Fähigkeiten [7][8][9].…”
Section: Schlussfolgerung Und Empfehlungenunclassified
“…Digitale Formate werden bereits seit vielen Jahren für das Medizinstudium entwickelt, wobei dies jedoch häufig für spezielle Fragestellungen erfolgte, wie die Verschreibung von Medikamenten, das Erlernen pädiatrischer Reanimationstechniken, die Bearbeitung umweltmedizinischer Fragen oder spezielle dermatologische oder physiologische Lehrinhalte [ 1 6 ]. Mit dem Auftreten der SARS-CoV-2-Pandemie wurde es jedoch erforderlich, Online-Unterricht nicht nur für einzelne, sondern für alle und sehr verschiedene Lehrveranstaltungen anzubieten, wobei Lehre, die traditionell der Interaktion mit Patientinnen oder Patienten bedarf, eine besondere Herausforderung an Lehrende und Studierende darstellt.…”
Section: Schlussfolgerung Und Empfehlungenunclassified
See 1 more Smart Citation